Environmentalism and its implications for education: a study of private schools in the Eastern Cape - Slade, Wilfred John (Rhodes University, Faculty of Education, Department of Education, 1992)
This study explores the extent to which the ethos and the basic approach to education taken by three Eastern Cape private schools influences the practice of environmental education within these schools. Their environmental education programmes are evaluated in terms of the guiding principles adopted by the international community in the 'Tbilisi Principles of Environmental Education'. An ethnographic approach was adopted for this research and findings are essentially descriptive and qualitative, with special regard to social structures and the attitudes of individuals within these structures.
Keywords: Environmental education -- Study and teaching -- South Africa; Environmental education -- Curricula -- South Africa; Private schools -- South Africa